Imminent : inside the Pentagon's hunt for UFOs - Elizondo, Luis (New York, NY : Wiliam Morrow & Company, an imprint of HarperCollinsPublishers, 2024)
"The former head of the Pentagon program responsible for the investigation of UFOs--now known as Unidentified Anomalous Phenomena (UAP)--reveals long-hidden truths with profound implications for not only national security but our understanding of the universe."--
Contains index.
Keywords: Elizondo, Luis; Unidentified flying objects -- Sightings and encounters -- United States; Unidentified flying objects -- Government policy -- United States; Official secrets -- United States